Sudan : First Review Under the Staff-Monitored Program-Press Release; Staff Report; and Statement by the Executive Director for Sudan. (IMF Staff Country Reports; Country Report, 2021)
The transitional government embarked on an IMF-supported Staff-Monitored Program (SMP) in 2020 to help address major macroeconomic imbalances caused by decades of mismanagement, lay the groundwork for inclusive growth, and establish a track record of sound policies required for eventual HIPC debt relief. The challenges facing the authorities remain significant, but there have been improvements in both the domestic and external environment. International efforts to support Sudan have gained momentum and were bolstered by the removal of Sudan from the U.S. list of State Sponsors of Terrorism (SSTL), and the identification of bridge financiers for Sudan's arrears clearance to IDA and the African Development Bank (AfDB). Meanwhile, the government has moved forward on important structural reforms, and on February 8, 2021 the signatories to the October peace agreement were brought into a newly formed cabinet which reaffirmed its commitment to the economic reform program.